An effectiveness of spiritual care educational program on nurses competence in Hospital USM: randomized control trial study - Abusafia, Ali H. A. (2020)
Spiritual care competence refers to a set of skills that are used in the nursing processes. These skills include therapeutic relationships between the nurse and patients. The main purpose of this study was to develop, validate and evaluate the effectiveness of the nursing spiritual care educational program on nurse’s competence in Hospital USM. This study was carried out in two phases. Phase I: development and validation of the spiritual care competence scale and nursing spiritual care module. For Phase I, a crosssectional study was conducted among 270 nurses from different wards and units in HUSM. The Forward-Backward method was used to translate the instrument of spiritual care competence scale from English to the Malay language. Face validity and confirmatory factor analysis (CFA), and reliability was conducted. Phase II: evaluating the effectiveness of the nursing spiritual care education module. A randomized control study was utilized among 58 and 60 nurses in the intervention and control group, respectively. The intervention group was given the nursing spiritual care education module. The control group received stander information from the hospital. Data collected by using the spiritual care competence scale Malay version. Data were analyzed using the SPSS version 24.0 for Windows. Two-way repeated measure ANOVA, and One-Way ANCOVA tests used. The result of phase I, revealed that the CFA results recommended some modifications. These modifications resulted in acceptable fit indices for the 6-factor model (RMSEA= 0.050, CFI= 0.900, TLI= 0.885, SRMR= 0.065). The Cronbach’s alpha value for SCCS-M was 0.926. The result of phase II revealed that; in the pre-test, the level of spiritual care competence in the intervention group was 70.7% (M=100.328 with SD= 8.480), and the level of spiritual care competence in the control group was 63.3% (M=100.067 with SD= 8.754). Meanwhile, in the post-test, the level of spiritual care competence in the intervention group was 84.5% (M=105.897 with SD =7.462) and the control group was 70% (M=101.183 with SD= 7.172). Also, there was a significant difference between the intervention and control groups within time (p = 0.001), between-group (p=0.037) and time*group interaction (P=0.001). Besides that, there is no significant mean differences of the sociodemographic factors (gender, marital status, education level and attendance spiritual care previous workshop) on the spiritual care competence among nurses in HUSM, when the age and experience years were controlled. The study concludes that results showed the nursing spiritual care module was effective in improving the competence of nurses in HUSM.